AI-enhanced language learning: The impact of Talkpal.AI on EFL undergraduate students’ English-speaking skills - Torkhani, Dina (American Journal of STEM Education, 2025)
This study was conducted to investigate the effectiveness of Talkpal.AI in improving fluency, pronunciation, vocabulary, and grammar among 40 pre-intermediate English as a Foreign Language (EFL) students in Kuwait. The participants were informed of the research objectives and implementation. A pretest-posttest design was used within a quasi-experimental design. Statistical analysis showed that students made significant improvements in posttest fluency, pronunciation, vocabulary, and grammar (p < 0.05). While the study’s limitations include sample size and lack of sample diversity, this finding emphasizes the potential of AI technologies such as Talkpal.AI in supporting and advancing language learning for EFL students